Aminoguanidine modified magnetic graphene oxide as a robust nanoadsorbent for efficient removal and extraction of chlorpyrifos residue from water. Issue 5 (October 2021) - Mahdavi, Vahideh; Taghadosi, Fatemeh; Dashtestani, Fariba; Bahadorikhalili, Saeed; Farimani, Mahdi Moridi; Ma'mani, Leila; Mousavi Khaneghah, Amin
Abstract: In this paper, graphene-based nanoadsorbent is designed and synthesized through the functionalization of magnetic graphene oxide by aminoguanidine (denoted AGu@mGO(R)). The graphene oxide (GO) was first fabricated from rice husk biomasses and modified Hammer's method. Then, co-precipitation of Fe 2+ and Fe 3+ onto GO in primary media resulted in magnetic graphene oxide (mGO), which was subsequently functionalized by aminoguanidine to form AGu@mGO(R) nanoparticles. The fabricated graphene-based nanoadsorbent was characterized by several techniques, including scanning electron microscopy (SEM), transmission electron microscopy (TEM), atomic force microscopy (AFM), dynamic light scattering (DLS), X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FT-IR), and vibrating sample magnetometer (VSM) analysis. AGu@mGO(R) efficiency was evaluated in removing chlorpyrifos, one of the most widely used pesticides from water and cucumber juice, as an actual sample. Different variables, including pH, concentration, temperature, exposure time, and amount of the adsorbent, were optimized on the efficiency of the adsorption activity of AGu@mGO(R) to obtain the most efficient pesticide removal. Isotherm, kinetic and thermodynamic of the adsorption processes were also evaluated. The chlorpyrifos desorption efficiency from AGu@mGO(R) was quantified by the HPLC-MS/MS method. The results showed the effective absorbent activity of AGu@mGO(R) on the removal of chlorpyrifos. Hence, this nonabsorbent would be used for the removal of the remained pesticide in agricultural wastewater. Additionally, the AGu@mGO(R) might be used for the quantification of pesticide residues in samples. Graphical Abstract: ga1 Highlights: Magnetic graphene-based nanoadsorbent was designed, synthesized, and characterized. The nanoadsorbent was evaluated for removal and extraction of chlorpyrifos residues from water. The cucumber was used as real sample for validation of the efficiency of nanoadsorbent in extraction of chlorpyrifos. The chlorpyrifos removal was quantified by the HPLC-MS/MS method.